Aquinas on imitation of nature : source of principles of moral action - Golubiewski, Wojciech (Washington, D.C. : The Catholic University of America Press, 2022)
"The author argues that it is possible to develop a metaphysical interpretation of Aquinas's doctrine of natural law that still deserves serious philosophical consideration today; examines Aquinas's theoretical reflections on the metaphysical and epistemological aspects of human natural goodness, applying them to moral contexts as found in the Secunda secundae"--
Intro -- Contents -- Foreword -- Acknowledgments -- Note on Thomas Aquinas's Works -- Abbreviations -- Introduction -- Chapter 1. Why Imitation of Nature Matters -- Chapter 2. Aquinas's Concept of the Imitation of Nature -- Chapter 3. Natural Teleology of Good -- Chapter 4. Imitation of the Divine Mind -- Chapter 5. Human Natural Goodness -- Chapter 6. Imitation of Nature in the Secunda Secundae -- Final Conclusion -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 28, 2022).
eBooks on EBSCOhost
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Thomas, -- Aquinas, Saint, -- 1225?-1274; Ethics; Act (Philosophy); Practical reason; Natural law; Philosophy of nature; Ethics; Morale; Action (Philosophie); Raison pratique; Droit naturel; Philosophie de la nature; ethics (philosophy); Metaethics